Potensi Potensi Ekstrak Etanol Kulit Buah Naga Merah (Hylocereus polyrhizus) sebagai Indikator pada Titrasi Asam Basa - Wikan Mahargyani; Wasdili, Fini Ainun Qolbi (JURNAL KESEHATAN KARTIKA, 2021)
Background : Indonesia is rich in colorful natural ingredients, with a variety of active ingredients. One that can be used is the color pigments found in plants. This pigment can be used as an acid-base indicator because it can give a different color to a certain pH value. One of the plants that has been reported to be potential as an indicator of acid-base was red dragon fruit (Hylocereus polyrhizus). The red color indicates the presence of anthocyanin compounds that can give different colors to acidic and alkaline pH. The acid-base indicators can be used to determined the occurrence of the equivalence point in the titration. Through this research, it was expected to know the potential of red dragon fruit peel ethanol extract as an alternative indicator in acid-base titration. Method: It was experimental research. The research began with extracting dragon fruit peels using ethanol as a solvent. Furthermore, the absorbance measurement of the extract was carried out to determine its maximum wavelength. This extract used as indicator in the titration for determine the concentration of hidrochloride acid. The results were compared with the determination of the concentration of the solution used the phenolphthalein indicator. Result : The extract obtained was red with maximum wavelength of 539 nm. The concentration of hidrochloric acid obtained for titration using the pp indicator was 0.0909 M and the extract indicator was 0,1011 M. Conclusion: This extract can be used in acid-base titrations with a color change from pink to peach at the end point of the titration.